KONTRUKSI REALITAS SOSIAL MANJOPUIK LIMAU PADA MASYARAKAT KENEGERIAN LUBUK JAMBI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Medio Aprima; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Tradition Manjopuik Limau (picked limes) is a tradition-laden society norms and values in each set of the procession. Messages in a procession Manjopuik Limau (picked limes) that are transmitted through symbols, objects, musical instruments all have meaning. In Kenegerian Lubuk Jambi, Manjopuik Limau (picked limes) has always been an annual event for the community, that is exactly on the eve of Idul Fitri. The existence of a tradition Manjopuik Limau as local wisdom raises a variety of views and meanings of society against the tradition. Daripenelitian destination is to know the process of externalization, objectification, and internalization of society Kenegerian Lubuk Jambi.This study uses qualitative research methods with the presentation of descriptive analysis. The informants are perpetrators of tradition, community, traditional leaders, government and traditional leaders as a supporter informant, the informant election tradition by choosing actors who have participated in Limau Manjopuik more than three times and through other considerations. Informants selected by purposive sampling. Data collection techniques used were observation, interviews, and documentation. technical validity of the data used in this study is an extension of participation and triangulation. The results obtained suggests that the process of externalization of the government which supports the tradition Manjopuik Limau this tradition by making the national agenda. Externalization process of society that they assume Manjopuik Limau important to continue to be preserved as a valuable asset. Community considers this tradition as upara as well as an entertainment center. The process of objectification of society explains that the tradition Manjopuik Lemons has experienced a shift, but even so the community. There is an organization that continues to support the Nature Batobo the continuity of tradition Manjopuik Limau to socialize about how the importance of maintaining the existing potential of cultural assets. Kenegerian Lubuk Jambi community also participated in the success of every implementation Manjopuik Limau tradition by providing assistance in the form of material and equipment required and lend. The internalization process Kenegerian society Lubuk Jambi namely Manjopuik Limau interpret tradition as tradition formed by the union and unity, as a venue for young people as well friendship society. Tradition Manjopuik Limau can also embrace young people in shaping socially correct